Band offset of vanadium-doped molybdenum oxide hole transport layer in organic photovoltaics. (August 2016) - Chang, Feng-Kuei; Huang, Yi-Chi; Jeng, Jiann-Shing; Chen, Jen-Sue
Highlights: V-doped molybdenum oxide films are synthesized via solution route. V-doped molybdenum oxide films are utilized as hole transport layer (HTL) in OPV. V0.05 MoOx device has smallest band offset between HOMO of P3HT and E v of HTL. V0.05 MoOx has the best solar cell performance among all when using as HTL in OPV. Abstract: Solution-processed vanadium-doped molybdenum oxide films (V)MoOx films with mole ratios of Mo:V = 1:0, 1:0.05, 1:0.2, 1:0.5, 0:1, are fabricated as hole transport layer (HTL) in organic photovoltaics with active layer blend comprising poly(3-hexylthiophene) (P3HT) and [6, 6]-phenyl-C61 butyric acid methyl ester (PCBM). The device structure is ITO/(V)MoOx /P3HT:PCBM/ZnO NP/Al, and the working area is 0.16 cm 2 . The result shows that the device using V0.05 MoOx HTL has the best performance, including power conversion efficiency of 2.16%, V oc of 0.6 V, J sc of 6.93 mA/cm 2, and FF of 51.9%. Using ultraviolet photoelectron spectroscopy (UPS), we can define the energy levels of valence band edge and Fermi level of (V)MoOx films. UPS analysis indicates that V0.05 MoOx has the smallest energy band offset between its valence band edge to the HOMO of P3HT, which is advantageous for hole transporting from P3HT to ITO anode via the V0.05 MoOx HTL. In addition, V0.05 MoOx film shows the lowest electrical resistivity among all (V)MoOx films, which is further beneficial for hole transportation.